A modified basalt fiber reinforcement and a light, thin and ultra-tough highway cover plate containing the modified basalt fiber reinforcement
By adding silica nanoparticle-polyurethane composite and nanosilica and silane coupling agent to the epoxy resin, the interface interaction between basalt fibers and epoxy resin is improved, and the problems of self-weight, easy to break and corrosion of reinforced concrete covers are solved, and the excellent mechanical and chemical properties of modified basalt fiber ribs are achieved, which extends the service life and enhances impact resistance.
Patent Information
- Application Number
- CN202411747971.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The reinforced concrete cover plate has problems such as heavy self-weight, easy to break, and easy to rust and corrode in alkaline environments. The interface performance between the basalt fibers and the epoxy resin matrix in the basalt fiber ribs needs to be improved. The epoxy resin has high brittleness after curing, and its impact and crack resistance are poor.
Add silica nanoparticle-polyurethane composite to the epoxy resin, and the polyurethane is coated with the surface of the nanosilicon dioxide particles to improve the flexibility and impact strength of the epoxy resin, and improve the interface interaction between basalt fibers and epoxy resin through nanosilicon dioxide and silane coupling agents, enhancing the performance stability of modified basalt fiber ribs.
The mechanical properties and chemical properties of modified basalt fiber reinforcement are significantly improved, the service life is extended, and the self-weight is reduced by improving the mechanical properties of the cover plate and the impact resistance is enhanced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular, relates to a modified basalt fiber reinforcement and a light, thin and ultra-tough highway cover plate containing the modified basalt fiber reinforcement. Background Art
[0002] As a component of highways, tunnel covers play an important role in highway operation and maintenance. At present, the most common tunnel covers are reinforced concrete covers, but they have many disadvantages: ① Heavy weight, the thickness of reinforced concrete tunnel covers is generally 80mm. Taking the most common cover as an example, the length and width are 750mm and 500mm respectively, and the weight of a single piece is 75kg, which makes installation and replacement difficult and inefficient; ② Easy to break, the concrete used for reinforced concrete covers is C30 and below, and the strength is relatively low. During transportation, installation and service, it is very easy to have broken edges and corners, which seriously affects the overall appearance and safety of use; ③ In an alkaline environment, steel bars are prone to rust and corrosion, which can easily cause the degradation of the mechanical properties of the structure and reduce durability, making it easy to fail.
[0003] Composite fiber reinforced cement cover plate has the advantages of light weight, high strength, corrosion resistance and fatigue resistance. It uses basalt fiber bars to replace steel bars, which can avoid the performance degradation caused by rust. At the same time, basalt fiber bars also have the advantages of wide sources, low prices and balanced performance. Basalt fiber bars are a new type of composite material formed by combining basalt fibers and synthetic resin matrix through pultrusion process. The main role of synthetic resin is bonding. Currently, the commonly used synthetic resins are epoxy resins. The interface performance between basalt fiber and epoxy resin matrix needs to be further improved. After curing, epoxy resin is brittle, and has poor impact resistance and crack resistance, which easily leads to the problem of insufficient performance stability of basalt fiber bars. Therefore, the present invention is to solve the above problems and provide a modified basalt fiber bar and a light and ultra-tough highway cover plate containing modified basalt fiber bars. Summary of the invention
[0004] The purpose of the present invention is to provide a modified basalt fiber reinforcement and a light, thin and ultra-tough highway cover plate containing the modified basalt fiber reinforcement. Silicon dioxide nanoparticles-polyurethane composites are added to epoxy resin to strengthen and toughen the epoxy resin, and polyurethane is coated on the surface of nano-silicon dioxide particles. On the one hand, the compatibility of silicon dioxide nanoparticles and epoxy resin can be improved, and the agglomeration of silicon dioxide nanoparticles in epoxy resin can be avoided. On the other hand, the excellent flexibility and elasticity of polyurethane can be utilized to further improve the flexibility of epoxy resin. The present invention utilizes the synergistic effect of polyurethane fiber and silicon dioxide nanoparticle-polyurethane composite to jointly improve the flexibility and impact strength of epoxy resin. The addition of nano-silicon dioxide particles and silane coupling agents improves the interface interaction between basalt fiber and epoxy resin, thereby improving the performance stability of basalt fiber reinforcement, so that the prepared modified basalt fiber reinforcement has excellent mechanical properties and chemical properties, and has a longer service life. The modified basalt fiber reinforcement is added to the cover plate to improve the mechanical properties of the cover plate.
[0005] The technical problem to be solved by the present invention is as follows: the reinforced concrete cover plate has the defects of being heavy, easy to be damaged and the steel bars are easy to rust and corrode in an alkaline environment. The composite fiber reinforced cement cover plate has the advantages of being light, high strength, corrosion-resistant and fatigue-resistant. The composite fiber reinforced cement cover plate uses basalt fiber bars instead of steel bars, which can reduce the weight of the cover plate and avoid the performance degradation caused by rust. However, the interface performance between the basalt fiber and the epoxy resin matrix in the basalt fiber bars needs to be further improved, and the epoxy resin is brittle after curing, and has poor impact resistance and crack resistance, which easily leads to the problem of insufficient performance stability of the basalt fiber bars.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A modified basalt fiber reinforcement, the preparation method comprising the following steps:
[0008] A1. Dispersing silica nanoparticles in a mixed solution of deionized water and anhydrous ethanol, then adding an isocyanate silane coupling agent, stirring and reacting at 60-70° C. for 4-6 hours, filtering, washing, and drying to obtain isocyanate-modified silica nanoparticles;
[0009] Furthermore, in step A1, the mass ratio of silica nanoparticles, deionized water, anhydrous ethanol and isocyanate silane coupling agent is (11-15): (300-380): (45-58): (10-20).
[0010] A2, adding diisocyanate to N, N-dimethylformamide, stirring and heating to 65°C under nitrogen protection, then dropping polyether diol, continuing to heat to 80-90°C for reaction for 2-3h to obtain a terminal isocyanate prepolymer; dropping diisopropanolamine into the terminal isocyanate prepolymer under ice water bath conditions, stirring for 30-40min after the addition is completed, to obtain a hydroxyl-terminated prepolymer; adding polyisocyanate and catalyst 1 to the hydroxyl-terminated prepolymer, reacting at 50-70°C for 13-15h to obtain an isocyanate-terminated polyurethane prepolymer;
[0011] In the above preparation process, diisocyanate and polyether diol are first reacted to generate an isocyanate-terminated prepolymer; then the isocyanate group of the isocyanate-terminated prepolymer is reacted with the imine group of diisopropanolamine to introduce two hydroxyl groups on the end group of the isocyanate-terminated prepolymer; then the two hydroxyl groups on the end group are reacted with triisocyanate to introduce four isocyanate groups on each end group to obtain a polyisocyanate-terminated polyurethane prepolymer.
[0012] Furthermore, in step A2, the molar ratio of polyether diol to diisocyanate is 1:(2-2.5).
[0013] Furthermore, in step A2, the molar ratio of the terminal isocyanate prepolymer to diisopropanolamine is 1:(2-2.3).
[0014] Furthermore, in step A2, the molar ratio of the hydroxyl-terminated prepolymer to the polyisocyanate is 1:(4-4.5).
[0015] Furthermore, in step A2, the mass of the catalyst is 0.05-0.15% of the total mass of the hydroxyl-terminated prepolymer and the polyisocyanate.
[0016] Furthermore, in step A2, the polyether diol includes at least one of polyethylene glycol, polypropylene glycol and polytetramethylene ether glycol.
[0017] Furthermore, in step A2, the diisocyanate includes at least one of hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate and methylcyclohexane diisocyanate.
[0018] Furthermore, in step A2, the polyisocyanate includes at least one of bicycloheptane triisocyanate, 1,6,11-undecane triisocyanate, 1,3,6-hexamethylene triisocyanate, and tris(isocyanate hexyl) isocyanurate.
[0019] Furthermore, in step A2, catalyst 1 is an organotin catalyst.
[0020] A3, dispersing isocyanate-modified silica nanoparticles in butanone, stirring and heating to 65-70°C under nitrogen protection, adding isocyanate-terminated polyurethane prepolymer, 3-aminopropyltrihydroxysilane and catalyst 2, and continuing to heat to 80-90°C and stirring for reaction for 3-5h to obtain a silica nanoparticle-polyurethane composite;
[0021] In the above preparation process, 3-aminopropyl trihydroxysilane is used as a bridge to graft the isocyanate-terminated polyurethane prepolymer and the silicon dioxide nanoparticles together through chemical bonds, so that the surface of the silicon dioxide nanoparticles is coated with polyurethane. Since 3-aminopropyl trihydroxysilane contains three hydroxyl groups, each end group of the isocyanate-terminated polyurethane prepolymer contains four isocyanate groups, thereby increasing the crosslinking density of the polyurethane coated on the surface of the silicon dioxide nanoparticles. In addition, the introduction of 3-aminopropyl trihydroxysilane provides Si-O segments, further improving flexibility.
[0022] Furthermore, in step A3, the mass ratio of isocyanate-modified silica nanoparticles, isocyanate-terminated polyurethane prepolymer, 3-aminopropyltrihydroxysilane and catalyst 2 is (12-15): (58-76): (33-39): (0.5-1.5).
[0023] Furthermore, in step A3, catalyst 2 is an organotin catalyst.
[0024] A4. Under nitrogen protection, the epoxy resin is stirred at 75-80° C. for 0.5-1 h, and then the silica nanoparticle-polyurethane composite and catalyst 3 are added and reacted for 2-4 h. After the reaction is completed, polyurethane fibers, a curing agent and a coupling agent are added and stirred evenly to obtain an epoxy resin mixture;
[0025] In the above preparation process, the isocyanate group on the silicon dioxide nanoparticle-polyurethane composite reacts with the hydroxyl group on the epoxy resin, so that the silicon dioxide nanoparticle-polyurethane composite and the epoxy resin are combined through chemical bonds, thereby improving the compatibility of the silicon dioxide nanoparticles and the epoxy resin. At the same time, the present invention also adds polyurethane fibers to the epoxy resin mixture, and uses the elasticity of the polyurethane fibers to toughen the epoxy resin. Since the epoxy resin mixture contains the polyurethane resin, the polyurethane fibers are evenly dispersed in the epoxy resin mixture.
[0026] Furthermore, in step A4, the epoxy resin is bisphenol A epoxy resin.
[0027] Furthermore, in step A4, the mass ratio of epoxy resin, silica nanoparticle-polyurethane composite, catalyst 3, polyurethane fiber, curing agent and coupling agent is (150-200): (13-16): (0.9-1.3): (4.5-9.5): (40-70): (20-40).
[0028] Furthermore, in step A4, the length of the polyurethane fiber is 3-6 mm.
[0029] Furthermore, in step A4, catalyst 3 is an organotin catalyst.
[0030] Furthermore, in step A4, the coupling agent is at least one of KH550, KH560, and KH570.
[0031] A5. After the basalt fiber is drawn, it is placed in an epoxy resin mixture for dipping to obtain a composite fiber reinforcement containing glue; after the composite fiber reinforcement containing glue is wound with a winding wire, it is sandblasted with quartz sand, and after the sandblasting is completed, it is cured and shaped to obtain a modified basalt fiber reinforcement.
[0032] Furthermore, in step A5, the diameter of the basalt fiber is 10-20 μm.
[0033] Furthermore, in step A5, the mass ratio of the basalt fiber and the epoxy resin mixture is (30-35): (115-130).
[0034] Furthermore, in step A5, during the curing and shaping process, the pultrusion speed is 590-640 mm / min, the traction force is 0.5-0.65 t, the pressure is 0.7-1.1 MPa, and the temperature is 100-120°C.
[0035] In the preparation process of the modified basalt fiber reinforcement, a silicon dioxide nanoparticle-polyurethane composite is added to the epoxy resin to strengthen and toughen the epoxy resin, and polyurethane is coated on the surface of the nano silicon dioxide particles. On the one hand, the compatibility of the silicon dioxide nanoparticles and the epoxy resin can be improved, and the silicon dioxide nanoparticles are prevented from agglomerating in the epoxy resin. On the other hand, the excellent flexibility and elasticity of the polyurethane can be utilized to further improve the flexibility of the epoxy resin. The polyurethane coated on the surface of the silicon dioxide nanoparticles of the present invention has a high cross-linking density, which improves the toughness of the polyurethane. The polyurethane contains polyisocyanate groups, and the isocyanate groups react with the epoxy resin to further improve the cross-linking density of the cured epoxy resin, thereby achieving a better toughening effect and significantly improving the impact resistance of the epoxy resin. The addition of silicon dioxide and silane coupling agent improves the interface interaction between the basalt fiber and the epoxy resin, thereby improving the performance stability of the modified basalt fiber reinforcement. The present invention also adds polyurethane fibers into the epoxy resin, and the polyurethane fibers and the silicon dioxide nanoparticle-polyurethane composite work synergistically to jointly improve the flexibility and impact resistance of the epoxy resin.
[0036] The present invention also provides a thin and light ultra-tough highway cover plate containing the modified basalt fiber reinforcement, comprising the following components in parts by weight: 20-30 parts of ordinary Portland cement, 25-45 parts of fly ash, 10-20 parts of silica fume, 5-10 parts of anhydrous calcium sulphoaluminate, 1-2 parts of polypropylene fiber, 1-2 parts of polyoxymethylene fiber, 0.5-2 parts of basalt fiber, 3-5 parts of acrylic emulsion, 0.5-1 parts of water reducer, 1-10 parts of machine-made sand, 5-10 parts of crushed stone, 15-20 parts of water, and 0.1-0.5 parts of nano-metakaolin.
[0037] The light, thin and ultra-tough highway cover plate containing modified basalt fiber bars comprises modified basalt fiber bars and basalt grids; each light, thin and ultra-tough highway cover plate containing modified basalt fiber bars contains three modified basalt fiber bars.
[0038] Furthermore, the diameter of the modified basalt fiber reinforcement is 4-8 mm.
[0039] Furthermore, the mesh size of the basalt grid is 20 mm×20 mm, and the thickness is 0.5-1 mm.
[0040] Furthermore, the length of the polypropylene fiber is 18-20 mm and the diameter is 0.3-0.5 mm.
[0041] Furthermore, the polyoxymethylene fiber has a length of 8-14 mm and a diameter of 0.1-0.3 mm.
[0042] Furthermore, the basalt fiber has a length of 3-20 mm and a diameter of 13-20 μm.
[0043] Furthermore, the fineness modulus of the manufactured sand is 2.5-2.6.
[0044] Furthermore, the particle size of the crushed stone is 5-10 mm.
[0045] Furthermore, the water reducing agent is a polycarboxylic acid-based high-performance water reducing agent.
[0046] Furthermore, the method for preparing the above-mentioned thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement comprises the following steps:
[0047] S1, weigh each raw material according to weight;
[0048] S2. Pour all the weighed dry materials except the fiber into the mixer, start the mixer, and stir for 1 minute;
[0049] S3. While the mixer is running, pour in the weighed water, acrylic emulsion and water reducer at a uniform speed and continue stirring for 2 minutes;
[0050] S4. While the mixer is running, add polypropylene fiber, polyoxymethylene fiber and basalt fiber at a uniform speed and continue stirring for 4 minutes until the slurry is uniform;
[0051] S5. Apply a release agent evenly to the mold and set it aside; prepare modified basalt fiber ribs and basalt grids according to the size matching the cover plate, place the mold on a vibration table, and turn on the vibration table;
[0052] S6. Inject the stirred slurry (fill half of the mold) into the mold. After the slurry is leveled, place three modified basalt fiber bars along the length of the cover plate. Then place the basalt grid on the modified basalt fiber bars and continue to inject slurry until the entire mold is filled.
[0053] S7. Transfer the mold filled with slurry to the curing platform, cover the cover plate together with the mold with plastic film; moisturize or steam cure for 24 hours, demould, and then neatly stack the cover plates on the pallet and pack them to obtain the light, thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement.
[0054] Beneficial effects of the present invention:
[0055] (1) In the technical solution of the present invention, a silica nanoparticle-polyurethane composite is added to the epoxy resin to strengthen and toughen the epoxy resin, and polyurethane is coated on the surface of the nano-silica particles. On the one hand, the compatibility of the silica nanoparticles with the epoxy resin can be improved, thereby avoiding the agglomeration of the silica nanoparticles in the epoxy resin. On the other hand, the excellent flexibility and elasticity of the polyurethane can be utilized to further improve the flexibility of the epoxy resin.
[0056] (2) In the technical solution of the present invention, the polyurethane coated on the surface of the silica nanoparticles has a high crosslinking density, which improves the toughness of the polyurethane. The polyurethane contains polyisocyanate groups, and the isocyanate groups react with the epoxy resin to further increase the crosslinking density of the cured epoxy resin, thereby achieving a better toughening effect and significantly improving the impact resistance of the epoxy resin.
[0057] (3) In the technical solution of the present invention, polyurethane fibers are added to the epoxy resin. The polyurethane fibers and the silica nanoparticle-polyurethane composite work synergistically to improve the flexibility and impact strength of the epoxy resin. The addition of nano-silica particles and silane coupling agents improves the interfacial interaction between basalt fibers and epoxy resin, thereby improving the performance stability of basalt fiber reinforcements, so that the prepared modified basalt fiber reinforcements have excellent mechanical and chemical properties and a longer service life. Adding the modified basalt fiber reinforcements to the cover plate can improve the mechanical properties of the cover plate and reduce its own weight. DETAILED DESCRIPTION
[0058] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] In each raw material of the following examples:
[0060] The average length of the polypropylene fibers was 19 mm and the average diameter was 0.4 mm.
[0061] The average length of the polyoxymethylene fibers is 10 mm and the average diameter is 0.2 mm.
[0062] The average length of basalt fibers is 12 mm and the average diameter is 17 μm.
[0063] The fineness modulus of artificial sand is 2.5.
[0064] The particle size of the crushed stone is 5-10 mm.
[0065] The average diameter of the modified basalt fiber reinforcement is 6 mm.
[0066] The mesh size of the basalt grille is 20mm×20mm and the thickness is 1mm.
[0067] Embodiment 1, a modified basalt fiber reinforcement, the preparation method comprises the following steps:
[0068] A1. Disperse 55 g of silica nanoparticles in a mixed solution of 1.5 L of deionized water and 225 mL of anhydrous ethanol, then add 50 g of 3-isocyanatepropyltrimethoxysilane, stir and react at 60 ° C for 4 h, filter, wash and dry to obtain isocyanate-modified silica nanoparticles;
[0069] A2, add 16.8g hexamethylene diisocyanate to 30mL In N,N-dimethylformamide, stir and heat to 65°C under nitrogen protection, then drop 200g of polypropylene glycol (the molar ratio of hexamethylene diisocyanate to polypropylene glycol is 2:1), continue to heat to 80°C for reaction for 2h to obtain a terminal isocyanate prepolymer; add diisopropanolamine dropwise to the terminal isocyanate prepolymer under ice water bath conditions (the molar ratio of the terminal isocyanate prepolymer to diisopropanolamine is 1:2), stir for 30min after the addition is completed to obtain a hydroxyl-terminated prepolymer; add dicycloheptane triisocyanate and dibutyltin dilaurate to the hydroxyl-terminated prepolymer (the molar ratio of the hydroxyl-terminated prepolymer to dicycloheptane triisocyanate is 1:4, and the mass of dibutyltin dilaurate is 0.05% of the total mass of the hydroxyl-terminated prepolymer and dicycloheptane triisocyanate), react at 50°C for 15h to obtain an isocyanate-terminated polyurethane prepolymer;
[0070] A3, 12g of isocyanate-modified silica nanoparticles were dispersed in 200mL of butanone, heated to 65°C under nitrogen protection, 58g of isocyanate-terminated polyurethane prepolymer, 33g of 3-aminopropyltrihydroxysilane and 0.5g of dibutyltin dilaurate were added, and the temperature was continued to rise to 80°C and stirred for reaction for 3h to obtain a silica nanoparticle-polyurethane composite;
[0071] A4. Under nitrogen protection, 150g of bisphenol A epoxy resin was stirred at 75°C for 0.5h, and then 13g of silica nanoparticle-polyurethane composite and 0.9g of dibutyltin dilaurate were added and reacted for 2h. After the reaction, 4.5g of polyurethane fiber, 40g of diethylenetriamine and 20g of KH550 were added and stirred evenly to obtain an epoxy resin mixture; wherein the average length of the polyurethane fiber was 4mm,
[0072] A5. After the basalt fiber is drawn, it is put into the epoxy resin mixture for dipping to obtain the adhesive-containing composite fiber reinforcement, and the mass ratio of the basalt fiber and the epoxy resin mixture is 30:115; the adhesive-containing composite fiber reinforcement is wound with 1000D polyester thread, and then sandblasted with quartz sand. After the sandblasting, it is cured and shaped. During the curing and shaping process, the pultrusion speed is 590mm / min, the traction force is 0.5t, the pressure is 0.7Mpa, and the temperature is 100℃ to obtain the modified basalt fiber reinforcement, wherein the average diameter of the basalt fiber is 13μm.
[0073] Embodiment 2, a modified basalt fiber reinforcement, the preparation method comprises the following steps:
[0074] A1. Disperse 65 g of silica nanoparticles in a mixed solution of 1.7 L of deionized water and 260 mL of anhydrous ethanol, then add 76 g of 3-isocyanatepropyltrimethoxysilane, stir and react at 65 °C for 5 h, filter, wash and dry to obtain isocyanate-modified silica nanoparticles;
[0075] A2. Add 16.8 g of hexamethylene diisocyanate to 30 mL of N,N-dimethylformamide, stir and heat to 65°C under nitrogen protection, then drop 220 g of polypropylene glycol (the molar ratio of hexamethylene diisocyanate to polypropylene glycol is 2.2:1), continue to heat to 85°C for 2 h to obtain a terminal isocyanate prepolymer; drop diisopropanolamine to the terminal isocyanate prepolymer in an ice water bath (the molar ratio of the terminal isocyanate prepolymer to diisopropanolamine is 1:2.2), stir for 35 min after the addition is completed in, to obtain a hydroxyl-terminated prepolymer; adding 1,3,6-hexamethylene triisocyanate and dibutyltin dilaurate to the hydroxyl-terminated prepolymer (the molar ratio of the hydroxyl-terminated prepolymer to 1,3,6-hexamethylene triisocyanate is 1:4.2, and the mass of dibutyltin dilaurate is 0.1% of the total mass of the hydroxyl-terminated prepolymer and 1,3,6-hexamethylene triisocyanate), reacting at 60° C. for 14 hours to obtain an isocyanate-terminated polyurethane prepolymer;
[0076] A3, 14g of isocyanate-modified silica nanoparticles were dispersed in 200mL of butanone, heated to 70°C under nitrogen protection, 65g of isocyanate-terminated polyurethane prepolymer, 34g of 3-aminopropyltrihydroxysilane and 1g of dibutyltin dilaurate were added, and the temperature was continued to be raised to 85°C and stirred for reaction for 4h to obtain a silica nanoparticle-polyurethane composite;
[0077] A4. Under nitrogen protection, 170 g of bisphenol A epoxy resin was stirred at 80° C. for 0.5 h, and then 14 g of silica nanoparticle-polyurethane composite and 1.1 g of dibutyltin dilaurate were added and reacted for 3 h. After the reaction, 7.3 g of polyurethane fiber, 58 g of diethylenetriamine and 30 g of KH560 were added and stirred to obtain an epoxy resin mixture; wherein the average length of the polyurethane fiber was 6 mm;
[0078] A5. After the basalt fiber is drawn, it is put into the epoxy resin mixture for dipping to obtain the adhesive-containing composite fiber reinforcement, and the mass ratio of the basalt fiber and the epoxy resin mixture is 32:126; the adhesive-containing composite fiber reinforcement is wound with 1000D polyester thread, and then sandblasted with quartz sand. After the sandblasting, it is cured and shaped. During the curing and shaping process, the pultrusion speed is 620mm / min, the traction force is 0.58t, the pressure is 0.9Mpa, and the temperature is 110℃ to obtain the modified basalt fiber reinforcement, wherein the average diameter of the basalt fiber is 17μm.
[0079] Comparative Example 1
[0080] Compared with Example 2, in Comparative Example 1, 1,3,6-hexamethylene triisocyanate in Step A2 is replaced by hexamethylene diisocyanate, and other steps and raw materials are the same as in Example 2.
[0081] Comparative Example 2
[0082] Compared with Example 2, in Comparative Example 2, 3-aminopropyltrihydroxysilane in Step A3 is replaced with dimethyldihydroxysilane, and other steps and raw materials are the same as in Example 2.
[0083] Comparative Example 3
[0084] Compared with Example 2, the silicon dioxide nanoparticles in Comparative Example 3 are not coated with polyurethane, and the other steps and raw materials are the same as those in Example 2.
[0085] Embodiment 3, a modified basalt fiber reinforcement, the preparation method comprises the following steps:
[0086] A1. Disperse 75 g of silica nanoparticles in a mixed solution of 1.9 L of deionized water and 290 mL of anhydrous ethanol, then add 100 g of 3-isocyanatepropyltrimethoxysilane, stir and react at 70 ° C for 6 h, filter, wash and dry to obtain isocyanate-modified silica nanoparticles;
[0087] A2. Add 16.8 g of hexamethylene diisocyanate to 30 mL of N,N-dimethylformamide, stir and heat to 65°C under nitrogen protection, then drop 250 g of polypropylene glycol (the molar ratio of hexamethylene diisocyanate to polypropylene glycol is 2.5:1), continue to heat to 90°C and react for 3 hours to obtain a terminal isocyanate prepolymer; add diisopropanolamine dropwise to the terminal isocyanate prepolymer under ice water bath conditions (the molar ratio of the terminal isocyanate prepolymer to diisopropanolamine is 1:2.3), stir for 40 minutes after the addition is completed n, to obtain a hydroxyl-terminated prepolymer; adding 1,6,11-undecane triisocyanate and dibutyltin dilaurate to the hydroxyl-terminated prepolymer (the molar ratio of the hydroxyl-terminated prepolymer to 1,6,11-undecane triisocyanate is 1:4.5, and the mass of dibutyltin dilaurate is 0.15% of the total mass of the hydroxyl-terminated prepolymer and 1,6,11-undecane triisocyanate), reacting at 70° C. for 15 hours to obtain an isocyanate-terminated polyurethane prepolymer;
[0088] A3, 15g of isocyanate-modified silica nanoparticles were dispersed in 200mL of butanone, heated to 70°C under nitrogen protection, 76g of isocyanate-terminated polyurethane prepolymer, 39g of 3-aminopropyltrihydroxysilane and 1.5g of dibutyltin dilaurate were added, and the temperature was continued to rise to 90°C and stirred for reaction for 5h to obtain a silica nanoparticle-polyurethane composite;
[0089] A4. Under nitrogen protection, 200 g of bisphenol A epoxy resin was stirred at 80° C. for 1 h, and then 16 g of silica nanoparticle-polyurethane composite and 1.3 g of dibutyltin dilaurate were added and reacted for 4 h. After the reaction, 9.5 g of polyurethane fiber, 70 g of diethylenetriamine and 40 g of KH570 were added and stirred to obtain an epoxy resin mixture; wherein the average length of the polyurethane fiber was 5 mm;
[0090] A5. After the basalt fiber is drawn, it is put into the epoxy resin mixture for dipping to obtain the adhesive-containing composite fiber reinforcement, and the mass ratio of the basalt fiber and the epoxy resin mixture is 35:130; the adhesive-containing composite fiber reinforcement is wound with 1000D polyester thread, and then sandblasted with quartz sand. After the sandblasting, it is cured and shaped. During the curing and shaping process, the pultrusion speed is 640mm / min, the traction force is 0.65t, the pressure is 1.1Mpa, and the temperature is 120℃ to obtain the modified basalt fiber reinforcement, wherein the average diameter of the basalt fiber is 20μm.
[0091] Example 4, a thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement, comprising the following components in parts by weight: 20 parts of ordinary Portland cement, 25 parts of fly ash, 10 parts of silica fume, 5 parts of anhydrous calcium sulphoaluminate, 1 part of polypropylene fiber, 1 part of polyoxymethylene fiber, 0.5 parts of basalt fiber, 3 parts of acrylic emulsion, 0.5 parts of polycarboxylic acid-based high-performance water reducer, 1 part of machine-made sand, 5 parts of crushed stone, 15 parts of water, and 0.1 parts of nano-metakaolin.
[0092] The light, thin and ultra-tough highway cover plate containing modified basalt fiber bars comprises modified basalt fiber bars and basalt grids; each light, thin and ultra-tough highway cover plate containing modified basalt fiber bars contains three modified basalt fiber bars.
[0093] The method for preparing the above-mentioned light, thin and ultra-tough highway cover plate with modified basalt fiber reinforcement comprises the following steps:
[0094] S1, weigh each raw material according to the above parts by weight;
[0095] S2. Pour all the weighed dry materials except the fiber into the mixer, start the mixer, and stir for 1 minute;
[0096] S3. While the mixer is running, pour in the weighed water, acrylic emulsion, and polycarboxylic acid high-performance water reducer at a uniform speed and continue stirring for 2 minutes;
[0097] S4. While the mixer is running, add polypropylene fiber, polyoxymethylene fiber and basalt fiber at a uniform speed and continue stirring for 4 minutes until the slurry is uniform;
[0098] S5. Apply a release agent evenly to the mold and set it aside; prepare modified basalt fiber ribs and basalt grids according to the size matching the cover plate, place the mold on a vibration table, and turn on the vibration table;
[0099] S6. Inject an appropriate amount of the stirred slurry (filling half of the mold) into the mold. After the slurry is leveled, place three modified basalt fiber bars prepared in Example 1 along the length direction of the cover plate, then place the basalt grid on the modified basalt fiber bars, and continue to inject the slurry until the entire mold is filled.
[0100] S7. Transfer the mold filled with slurry to the curing platform, cover the cover plate together with the mold with plastic film; moisturize or steam cure for 24 hours, demould, and then neatly stack the cover plates on the pallet and pack them to obtain the light, thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement.
[0101] Example 5 A thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement comprises the following components in parts by weight: 26 parts of ordinary Portland cement, 33 parts of fly ash, 14 parts of silica fume, 8 parts of anhydrous calcium sulphoaluminate, 1.5 parts of polypropylene fiber, 1 part of polyoxymethylene fiber, 1.5 parts of basalt fiber, 4 parts of acrylic emulsion, 0.7 parts of polycarboxylic acid-based high-performance water reducer, 6 parts of machine-made sand, 8 parts of crushed stone, 17 parts of water, and 0.3 parts of nano-metakaolin.
[0102] The light, thin and ultra-tough highway cover plate containing modified basalt fiber bars comprises modified basalt fiber bars and basalt grids; each light, thin and ultra-tough highway cover plate containing modified basalt fiber bars contains three modified basalt fiber bars.
[0103] The method for preparing the above-mentioned light, thin and ultra-tough highway cover plate with modified basalt fiber reinforcement comprises the following steps:
[0104] S1, weigh each raw material according to the above parts by weight;
[0105] S2. Pour all the weighed dry materials except the fiber into the mixer, start the mixer, and stir for 1 minute;
[0106] S3. While the mixer is running, pour in the weighed water, acrylic emulsion, and polycarboxylic acid high-performance water reducer at a uniform speed and continue stirring for 2 minutes;
[0107] S4. While the mixer is running, add polypropylene fiber, polyoxymethylene fiber and basalt fiber at a uniform speed and continue stirring for 4 minutes until the slurry is uniform;
[0108] S5. Apply a release agent evenly to the mold and set it aside; prepare modified basalt fiber ribs and basalt grids according to the size matching the cover plate, place the mold on a vibration table, and turn on the vibration table;
[0109] S6. Inject an appropriate amount of the stirred slurry (filling half of the mold) into the mold. After the slurry is leveled, place three modified basalt fiber bars prepared in Example 2 along the length direction of the cover plate, then place the basalt grid on the modified basalt fiber bars, and continue to inject the slurry until the entire mold is filled;
[0110] S7. Transfer the mold filled with slurry to the curing platform, cover the cover plate together with the mold with plastic film; moisturize or steam cure for 24 hours, demould, and then neatly stack the cover plates on the pallet and pack them to obtain the light, thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement.
[0111] Example 6, a thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement, comprising the following components in parts by weight: 30 parts of ordinary Portland cement, 45 parts of fly ash, 20 parts of silica fume, 10 parts of anhydrous calcium sulphoaluminate, 2 parts of polypropylene fiber, 2 parts of polyoxymethylene fiber, 2 parts of basalt fiber, 5 parts of acrylic emulsion, 1 part of polycarboxylic acid-based high-performance water reducer, 10 parts of machine-made sand, 10 parts of crushed stone, 20 parts of water, and 0.5 parts of nano-metakaolin.
[0112] The light, thin and ultra-tough highway cover plate containing modified basalt fiber bars comprises modified basalt fiber bars and basalt grids; each light, thin and ultra-tough highway cover plate containing modified basalt fiber bars contains three modified basalt fiber bars.
[0113] The method for preparing the above-mentioned light, thin and ultra-tough highway cover plate with modified basalt fiber reinforcement comprises the following steps:
[0114] S1, weigh each raw material according to the above parts by weight;
[0115] S2. Pour all the weighed dry materials except the fiber into the mixer, start the mixer, and stir for 1 minute;
[0116] S3. While the mixer is running, pour in the weighed water, acrylic emulsion, and polycarboxylic acid high-performance water reducer at a uniform speed and continue stirring for 2 minutes;
[0117] S4. While the mixer is running, add polypropylene fiber, polyoxymethylene fiber and basalt fiber at a uniform speed and continue stirring for 4 minutes until the slurry is uniform;
[0118] S5. Apply a release agent evenly to the mold and set it aside; prepare modified basalt fiber ribs and basalt grids according to the size matching the cover plate, place the mold on a vibration table, and turn on the vibration table;
[0119] S6. Inject an appropriate amount of stirred slurry (filling half of the mold) into the mold. After the slurry is leveled, place three modified basalt fiber bars prepared in Example 3 along the length direction of the cover plate, then place the basalt grid on the modified basalt fiber bars, and continue to inject slurry until the entire mold is filled;
[0120] S7. Transfer the mold filled with slurry to the curing platform, cover the cover plate together with the mold with plastic film; moisturize or steam cure for 24 hours, demould, and then neatly stack the cover plates on the pallet and pack them to obtain the light, thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement.
[0121] Comparative Example 4
[0122] Compared with Example 5, the modified basalt fiber tendons in Comparative Example 4 use the material prepared in Comparative Example 1, and the other steps and raw materials are the same as those in Example 5.
[0123] Comparative Example 5
[0124] Compared with Example 5, the modified basalt fiber reinforcement in Comparative Example 5 uses the material prepared in Comparative Example 2, and the other steps and raw materials are the same as those in Example 5.
[0125] Comparative Example 6
[0126] Compared with Example 5, the modified basalt fiber tendons in Comparative Example 6 use the material prepared in Comparative Example 3, and the other steps and raw materials are the same as those in Example 5.
[0127] Performance Testing
[0128] (1) The modified basalt fiber bars prepared in Examples 1-3 and Comparative Examples 1-3 were tested for tensile strength and elastic modulus according to JT / T 776.4-2010:
[0129] Table 1
[0130]
[0131] It can be seen from the data in Table 1 that the modified basalt fiber tendons prepared by the present invention have excellent tensile strength and elastic modulus. Comparing the data of Example 2 with Comparative Examples 1 and 2, it can be seen that replacing 1,3,6-hexamethylene triisocyanate with hexamethylene diisocyanate or replacing 3-aminopropyl trihydroxysilane with dimethyl dihydroxysilane will reduce the crosslinking density of the resin, thereby causing a decrease in tensile strength and elastic modulus. Comparing the data of Example 2 with Comparative Example 3, it can be seen that since the surface of the nano-silica particles is not coated with polyurethane, the tensile strength and elastic modulus are significantly reduced.
[0132] (2) The cover plates of Example 4-6 and Comparative Example 4-6, which were cured and had a length, width and height of 750 mm × 500 mm × 20 mm and a weight of 14.7 kg, were subjected to performance testing.
[0133] Impact resistance test: The cement fiber cover is placed horizontally with simple supports on both sides and a net span of 65cm. A 5Kg steel ball is freely dropped from a height of 1.5m to impact the cement cover multiple times without breaking.
[0134] Crack load and failure load: The test method refers to the "Standard Technical Bid for Cable Trench Covers" of China Southern Power Grid:
[0135] Table 2
[0136]
[0137] It can be seen from the data in Table 2 that the cover plate prepared by the present invention has excellent mechanical properties. Comparing the data of Example 5 with Comparative Examples 4 and 5, it can be seen that replacing 1,3,6-hexamethylene triisocyanate with hexamethylene diisocyanate or replacing 3-aminopropyl trihydroxysilane with dimethyl dihydroxysilane will reduce the crosslinking density of the resin, and the tensile strength and elastic modulus of the basalt fiber tendons will decrease, resulting in a decrease in the impact resistance, crack load and failure load of the cover plate. Comparing the data of Example 5 and Comparative Example 6, it can be seen that since the surface of the nano-silica particles is not coated with polyurethane, the tensile strength and elastic modulus of the basalt fiber tendons are significantly reduced, thereby significantly reducing the impact resistance, crack load and failure load of the cover plate.
[0138] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0139] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A modified basalt fiber reinforcement, characterized in that: The preparation method comprises the following steps: A1. Dispersing silica nanoparticles in a mixed solution of deionized water and anhydrous ethanol, then adding an isocyanate silane coupling agent, stirring and reacting at 60-70° C. for 4-6 hours, filtering, washing, and drying to obtain isocyanate-modified silica nanoparticles; A2, adding diisocyanate to N, N-dimethylformamide, stirring and heating to 65°C under nitrogen protection, then dropping polyether diol, continuing to heat to 80-90°C for reaction for 2-3h to obtain a terminal isocyanate prepolymer; dropping diisopropanolamine into the terminal isocyanate prepolymer under ice water bath conditions, stirring for 30-40min after the addition is completed, to obtain a hydroxyl-terminated prepolymer; adding polyisocyanate and catalyst 1 to the hydroxyl-terminated prepolymer, reacting at 50-70°C for 13-15h to obtain an isocyanate-terminated polyurethane prepolymer; A3, dispersing isocyanate-modified silica nanoparticles in butanone, stirring and heating to 65-70°C under nitrogen protection, adding isocyanate-terminated polyurethane prepolymer, 3-aminopropyltrihydroxysilane and catalyst 2, and continuing to heat to 80-90°C and stirring for reaction for 3-5h to obtain a silica nanoparticle-polyurethane composite; A4. Under nitrogen protection, the epoxy resin is stirred at 75-80° C. for 0.5-1 h, and then the silica nanoparticle-polyurethane composite and catalyst 3 are added and reacted for 2-4 h. After the reaction is completed, polyurethane fibers, a curing agent and a coupling agent are added and stirred evenly to obtain an epoxy resin mixture; A5. After the basalt fiber is drawn, it is placed in an epoxy resin mixture for dipping to obtain a composite fiber reinforcement containing glue; after the composite fiber reinforcement containing glue is wound with a winding wire, it is sandblasted with quartz sand, and after the sandblasting is completed, it is cured and shaped to obtain a modified basalt fiber reinforcement; In the step A2, the polyisocyanate includes at least one of bicycloheptane triisocyanate, 1,6,11-undecane triisocyanate, 1,3,6-hexamethylene triisocyanate, and tris(isocyanate hexyl) isocyanurate.
2. The modified basalt fiber reinforcement according to claim 1, characterized in that: The diameter of the modified basalt fiber reinforcement is 4-8 mm.
3. The modified basalt fiber reinforcement according to claim 1, characterized in that: In the step A1, the mass ratio of the silicon dioxide nanoparticles, deionized water, anhydrous ethanol and isocyanate silane coupling agent is (11-15): (300-380): (45-58): (10-20).
4. The modified basalt fiber reinforcement according to claim 1, characterized in that: In the step A2, the molar ratio of the polyether diol to the diisocyanate is 1:(2-2.5), the molar ratio of the terminal isocyanate prepolymer to the diisopropanolamine is 1:(2-2.3), and the molar ratio of the hydroxyl-terminated prepolymer to the polyisocyanate is 1:(4-4.5).
5. The modified basalt fiber reinforcement according to claim 1, characterized in that: In the step A3, the mass ratio of isocyanate-modified silica nanoparticles, isocyanate-terminated polyurethane prepolymer, 3-aminopropyltrihydroxysilane and catalyst 2 is (12-15): (58-76): (33-39): (0.5-1.5).
6. The modified basalt fiber reinforcement according to claim 1, characterized in that: In the step A4, the mass ratio of epoxy resin, silica nanoparticle-polyurethane composite, catalyst 3, polyurethane fiber, curing agent and coupling agent is (150-200): (13-16): (0.9-1.3): (4.5-9.5): (40-70): (20-40).
7. The modified basalt fiber reinforcement according to claim 1, characterized in that: In the step A5, during the curing and shaping process, the pultrusion speed is 590-640 mm / min, the traction force is 0.5-0.65 t, the pressure is 0.7-1.1 MPa, and the temperature is 100-120°C.
8. A light, thin and ultra-tough highway cover plate containing the modified basalt fiber reinforcement according to any one of claims 1 to 7, characterized in that: The invention comprises the following components in parts by weight: 20-30 parts of ordinary Portland cement, 25-45 parts of fly ash, 10-20 parts of silica fume, 5-10 parts of anhydrous calcium sulphoaluminate, 1-2 parts of polypropylene fiber, 1-2 parts of polyoxymethylene fiber, 0.5-2 parts of basalt fiber, 3-5 parts of acrylic emulsion, 0.5-1 parts of water reducing agent, 1-10 parts of machine-made sand, 5-10 parts of crushed stone, 15-20 parts of water, and 0.1-0.5 parts of nano-metakaolin; The light, thin and ultra-tough highway cover plate containing modified basalt fiber bars comprises modified basalt fiber bars and basalt grids; each light, thin and ultra-tough highway cover plate containing modified basalt fiber bars contains three modified basalt fiber bars.
9. The light, thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement according to claim 8, characterized in that: The preparation method comprises the following steps: S1, weigh each raw material according to weight; S2. Pour all the weighed dry materials except the fiber into the mixer, start the mixer, and stir for 1 minute; S3. While the mixer is running, pour in the weighed water, acrylic emulsion and water reducer at a uniform speed and continue stirring for 2 minutes; S4. While the mixer is running, add polypropylene fiber, polyoxymethylene fiber and basalt fiber at a uniform speed and continue stirring for 4 minutes until the slurry is uniform; S5. Apply a release agent evenly to the mold and set it aside; prepare modified basalt fiber ribs and basalt grids according to the size matching the cover plate, place the mold on a vibration table, and turn on the vibration table; S6. Inject the stirred slurry into the mold to fill half of the mold. After the slurry is leveled, place three modified basalt fiber bars along the length of the cover plate. Then place the basalt grid on the modified basalt fiber bars and continue to inject slurry until the entire mold is filled. S7. Transfer the mold filled with slurry to the curing platform, cover the cover plate together with the mold with plastic film; moisturize or steam cure for 24 hours, demould, and then neatly stack the cover plates on the pallet and pack them to obtain the light, thin and ultra-tough highway cover plate containing modified basalt fiber reinforcement.
Citation Information
Patent Citations
Nano-modification polyurethane fibre material and preparation method thereof
CN106757488A
Two-pack building-reinforcing agent and main agent for the same
JP2003213136A